Medium Effects in Photoinduced Electron Transfer Reactions - Paul Suppan (CHIMIA)
The transfer of an electron between two molecules is a fundamental chemical process of great significance in biochemistry as well as in general chemistry. Electron transfer reactions can be induced by the absorption of light – as in photosynthesis – so that one of the molecules reacts through an electronically excited state; a net storage of chemical energy may then take place. When electron transfer involves molecules in condensed phase, the role of the liquid or solid medium must be considered. In the first place, a polar solvent may promote electron transfer through the stabilization of ion pairs and the separation of ions; but if the polar solvent must reorganize prior to the reaction, then an activation barrier will exist against electron transfer in polar solvents. – This article gives a critical review of this field, with some novel ideas concerning the role of the medium (liquid solvent or solid matrix) in the overall energy balance of electron transfer, in the kinetics of the reaction, and in the further process of charge separation. It is suggested in particular that no dielectric screening by a polar solvent can exist when ions are formed in direct contact; and that the extensive reorganization of the solvent prior to electron transfer is so unlikely as to be discounted. In these respects the model presented in this article diverges from the commonly accepted models of Weller and of Marcus and Hush. In the Conclusion section some areas of particular importance for further research in this field are outlined.